2015
DOI: 10.1073/pnas.1423301112
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral incompatibility gene ui1.1 encodes an S-locus F-box protein expressed in pollen of Solanum species

Abstract: Unilateral interspecific incompatibility (UI) is a postpollination, prezygotic reproductive barrier that prevents hybridization between related species when the female parent is self-incompatible (SI) and the male parent is self-compatible (SC). In tomato and related Solanum species, two genes, ui1.1 and ui6.1, are required for pollen compatibility on pistils of SI species or hybrids. We previously showed that ui6.1 encodes a Cullin1 (CUL1) protein. Here we report that ui1.1 encodes an S-locus F-box (SLF) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(119 citation statements)
references
References 40 publications
5
113
0
1
Order By: Relevance
“…(Box 2; Williams et al, 2014a;Kubo et al, 2015). Consistent with this finding, the genome sequence of SC Solanum pennellii LA0716 (a recently derived SC accession of an otherwise SI species) contains an array of 23 SLF genes, while the SC tomato genome shows, at most, four intact genes (Bolger et al, 2014;Li and Chetelat, 2015).…”
Section: S-rnase-based Simentioning
confidence: 60%
See 1 more Smart Citation
“…(Box 2; Williams et al, 2014a;Kubo et al, 2015). Consistent with this finding, the genome sequence of SC Solanum pennellii LA0716 (a recently derived SC accession of an otherwise SI species) contains an array of 23 SLF genes, while the SC tomato genome shows, at most, four intact genes (Bolger et al, 2014;Li and Chetelat, 2015).…”
Section: S-rnase-based Simentioning
confidence: 60%
“…A loss-of-function study showed that CUL1 also functions in SI (Li and Chetelat, 2014). Recently, the ui1.1 factor was identified as a single SLF gene, SLF-23 (Li and Chetelat, 2015). Thus, SI and UI utilize shared factors for both the pollen-and pistil-side functions and are characterized by a pistil-barrier/pollen-resistance architecture.…”
Section: Si and Interspecific Incompatibility: A Common Toolkitmentioning
confidence: 99%
“…McClure et al (1989) and Sijacic et al (2004) also attributed unilateral incompatibility in Solanum and other Solanaceae to the S-RNase-based, gametophytic type, in which S-specificity is determined by S-RNases in the pistil and S-locus F-box proteins (SLFs) in pollen. Li and Chetelat (2014) further emphasized that pollen rejection in UI involves biochemical mechanisms related to SI (self-incompatibility). According to Li and Chetelat (2014), ui1.1, a pollen UI factor in tomato, encodes an S-locus Fbox protein that is homologous to an SI gene that in Petunia determines pollen specificity.…”
Section: Hybridization Between Cultivated Eggplant Species and Their mentioning
confidence: 99%
“…Li and Chetelat (2014) further emphasized that pollen rejection in UI involves biochemical mechanisms related to SI (self-incompatibility). According to Li and Chetelat (2014), ui1.1, a pollen UI factor in tomato, encodes an S-locus Fbox protein that is homologous to an SI gene that in Petunia determines pollen specificity. Thus, pollen rejection in UI involves biochemical mechanisms related to SI.…”
Section: Hybridization Between Cultivated Eggplant Species and Their mentioning
confidence: 99%
“…This co‐variation between SI and II has been termed the SI × SC rule, and results in an asymmetric barrier to hybridization called ‘unilateral incompatibility’. In some systems, such as Solanum (de Nettancourt, ; Hancock et al ., ; Li & Chetelat, , , ) and Nicotiana (Murfett et al ., ), unilateral incompatibility arises because the genes causing SI also cause II. A pleiotropic link between SI and II implies that if selection acts on one incompatibility, the other type of incompatibility will show a correlated response to selection.…”
Section: Introductionmentioning
confidence: 99%